Aortic Valve Surgery in Patients Over 75 Years Old: Early Results and Predictors of Hospital Mortality - Selman Dumani; Laureta Dibra; Ermal Likaj; Saimir Kuci; Edlira Rruci; Aferdita Veseli; Klodian Krakulli; Andi Kacani; Edvin Prifti; Ilir Tanku; Devis Pellumbi; Alessia Mehmeti; et al. (Albanian Journal of Trauma and Emergency Surgery)
Background: Aortic valve surgery is the most essential part of worldwide heart valve surgery. In recent decades, the patient profile has changed even in our country, with the age of patients undergoing aortic valve surgery increasing significantly.